Quality of the fibrinogen index in freeze-dried plasma for external blood coagulation testing programs - Thi Hong Nguyen; Thanh Tung Tran; Thi Diem Phuc Huynh; Quang Huy Vu (Revista Cubana de Medicina Militar, 2025)
Background: Lyophilized plasma is widely used in external quality assessment for fibrinogen testing, where sample homogeneity and stability are critical. This study evaluated these factors, addressing challenges in sample preparation to enhance the quality of medical services.